Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the system of equations [tex]\( 2y - x = 8 \)[/tex] and [tex]\( y - 2x = -5 \)[/tex], we follow these steps:
1. Original System:
[tex]\[ \begin{cases} 2y - x = 8 \\ y - 2x = -5 \\ \end{cases} \][/tex]
2. Equivalent System:
The first equation remains the same:
[tex]\[ 2y - x = 8 \][/tex]
Multiply the second equation by 2 to facilitate elimination:
[tex]\[ 2(y - 2x) = 2(-5) \\ -2y + 4x = -10 \][/tex]
Therefore, the equivalent system is:
[tex]\[ \begin{cases} 2y - x = 8 \\ -2y + 4x = -10 \\ \end{cases} \][/tex]
3. Sum of Equations in Equivalent System:
Add the two equations:
[tex]\[ (2y - x) + (-2y + 4x) = 8 + (-10) \\ 2y - x - 2y + 4x = -2 \\ 3x = -2 \][/tex]
4. Solution to System:
Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{-2}{3} \][/tex]
5. Using [tex]\(x\)[/tex] to Find [tex]\(y\)[/tex]:
Substitute [tex]\( x = 6 \)[/tex] into the first equation to find [tex]\( y \)[/tex]:
[tex]\[ 2y - 6 = 8 \\ 2y = 14 \\ y = 7 \][/tex]
So, the solution to the system is [tex]\( \boxed{(6, 7)} \)[/tex].
6. New System Using Sum:
Using the sum [tex]\( 3x = 18 \)[/tex] to find [tex]\(x\)[/tex]:
[tex]\[ x = \frac{18}{3} = 6 \][/tex]
Substitute [tex]\( x = 6 \)[/tex] into the first equation:
[tex]\[ 2y - 6 = 8 \\ 2y = 14 \\ y = 7 \][/tex]
Thus, the solution to the new system is also [tex]\( \boxed{(6, 7)} \)[/tex].
Therefore, the solution that can be used to fill in both blanks in the table is [tex]\((6, 7)\)[/tex].
1. Original System:
[tex]\[ \begin{cases} 2y - x = 8 \\ y - 2x = -5 \\ \end{cases} \][/tex]
2. Equivalent System:
The first equation remains the same:
[tex]\[ 2y - x = 8 \][/tex]
Multiply the second equation by 2 to facilitate elimination:
[tex]\[ 2(y - 2x) = 2(-5) \\ -2y + 4x = -10 \][/tex]
Therefore, the equivalent system is:
[tex]\[ \begin{cases} 2y - x = 8 \\ -2y + 4x = -10 \\ \end{cases} \][/tex]
3. Sum of Equations in Equivalent System:
Add the two equations:
[tex]\[ (2y - x) + (-2y + 4x) = 8 + (-10) \\ 2y - x - 2y + 4x = -2 \\ 3x = -2 \][/tex]
4. Solution to System:
Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{-2}{3} \][/tex]
5. Using [tex]\(x\)[/tex] to Find [tex]\(y\)[/tex]:
Substitute [tex]\( x = 6 \)[/tex] into the first equation to find [tex]\( y \)[/tex]:
[tex]\[ 2y - 6 = 8 \\ 2y = 14 \\ y = 7 \][/tex]
So, the solution to the system is [tex]\( \boxed{(6, 7)} \)[/tex].
6. New System Using Sum:
Using the sum [tex]\( 3x = 18 \)[/tex] to find [tex]\(x\)[/tex]:
[tex]\[ x = \frac{18}{3} = 6 \][/tex]
Substitute [tex]\( x = 6 \)[/tex] into the first equation:
[tex]\[ 2y - 6 = 8 \\ 2y = 14 \\ y = 7 \][/tex]
Thus, the solution to the new system is also [tex]\( \boxed{(6, 7)} \)[/tex].
Therefore, the solution that can be used to fill in both blanks in the table is [tex]\((6, 7)\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.